Pengaruh Profesionalisme dan Perilaku Disfungsional Auditor Pada Kualitas Audit dengan Kepuasan Kerja Sebagai Variabel Moderasi - Purwaningsih, Putu Ayu Velia; Suputra, I Dewa Gede Dharma (E-Jurnal Akuntansi, 2018)
The purpose of this study to determine the effect of auditor professionalism and dysfunctional behavior of auditors to audit quality with job satisfaction as a moderation variable at Public Accounting Firm in Bali.Penelitian conducted at Public Accounting Firm in Bali with nine offices in 2017 with the number of auditors as many as 74 people as sample through saturated sample method. Data collection was done by distributing questionnaires. 48 questionnaires were analyzed through moderation regression analysis (MRA). Based on the analysis result, professionalism variable had a significant positive effect on audit quality at Public Accounting Firm in Bali. Dysfunctional behavior of auditors has a significant negative effect on audit quality in Public Accounting Firm in Bali. Job satisfaction has a significant positive effect on audit quality at Public Accounting Firm in Bali. Job satisfaction moderates the positive influence of professionalism on audit quality at Public Accounting Firm in Bali. Job satisfaction moderates the negative effect of auditor dysfunctional behavior on audit quality at Public Accounting Firm in Bali.